PERLINDUNGAN HUKUM TERHADAP PARA PIHAK YANG PERKAWINANNYA DIBATALKAN (Analisis Putusan Pengadilan Tinggi Agama Nomor 47/Pdt.G/2011/PTA.Pbr) - PUTRI DEWI TULUS (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Utary Maharany Barus2. Yefrizawati3. Idha Aprilyana Sembiring There are two factors which ca revoke a marriage: violation against the procedure such as the requirements for the presence of Wali Nikah (male next of kin and guardian whose consent is required for the marriage) and witnesses is not fulfilled, or it is carried out by unauthorized a marriage registrar and the violation against the marriage materials as it is stipulated in Article 22 of Marriage Law and Article 70 until Article 72 of KHI. Legal protection for those whose marriages are revoked stipulated in Article 28, paragraph 2, point b of Law No. 1/1974 on Marriage and in Article 75 and 76 of KHI in which the revocation is not put into effect retroactively on children, and the married couple who have good faith and the third party whose rights are fulfilled with good faith. The marriage between defendant I and defendant II is carried out is beyond the authority of Wali Nikah. It is carried out by a marriage registrar in Payung Sekaki Subdistrict as Wali Hakim (a person, appointed by the Court, who is not related to the bride) who marries defendant I and defendant II; therefore, the judge hands down a Verdict which revokes the marriage in which it is performed by a Wali Hakim who has no right as it is stipulated in Article 26, paragraph 1 of Law No. 1/1974 on Marriage and Article 71 of KHI.Keywords: Legal Protection, Marriage, Revocation of Marriage